SURGICAL TECHNIQUES FOR SPORTS HERNIA REPAIR IN ATHLETES - MINIMIZING COMPLICATIONS AND ENSURING SAFE RETURN TO SPORT - Marcin Markowski; Kacper Zielonka; Joanna Jasińska; Bartosz Dądela; Natalia Śliwa; Eliza Kawalska; Sara Langner; Szymon Gnitecki; Szymon Janczura; Maciej Borowski (International Journal of Innovative Technologies in Social Science, 2025)
Athletic pubalgia or sports hernia is a multifactorial and dynamic condition frequently found in sportsmen engaged in high-level sports involving sudden change of direction with repetitive stress to the groin. The present surgical strategies to repair sports hernia in sportsmen are discussed below, keeping in mind the precautions against complications and early safe return to sport. The pathophysiology of sports hernias is composed of core instability, recurrent microtrauma, and potential systemic and genetic connective tissue disorders. Proper diagnosis - aided by both physical examination and high-technology imaging studies such as MRI and dynamic USG - is needed to distinguish true hernias from the myriad other causes of groin pain. While conservative treatment in certain cases may be beneficial, surgery is the yardstick for symptomatic or refractory athletes. The open and laparoscopic techniques, including the Lichtenstein, TAPP, and TEP techniques, share similar benefits based on anatomical and technical criteria. Innovations such as robot-assisted repair and biomaterial creation of biocompatible mesh material, i.e., self-adhesive and biologic types, have also promoted good results. Prevention of early postoperative complication, in the form of chronic pain and infection, is founded on careful technique selection, mesh optimization, and reduction in risk factors. A carefully planned, phase-specific rehabilitation protocol - early mobilization, core strengthening, and sport-specific training is crucial to successful functional recovery. Last but not least, success with surgery relies on careful patient selection, rehabilitation compliance, and coordination of a multidisciplinary provider. This combined strategy provides superb rates of return to play and results on the long term from a clinical point of view, such that surgical treatment is an extremely effective method of treatment of sports hernia in sporting people.